Citrus leaf nutrient status: A critical evaluation of guidelines for optimal yield in Israel1. Issue 3 (21st May 2013) - Raveh, Eran
Abstract Maintaining orchards with trees at optimal leaf nutrient concentrations is one of the key issues for maximizing yield. Experiments for evaluating and updating guidelines are very rare since they require several years of field experiments with mature fruit‐bearing trees. In the present paper, we first evaluated the Israeli guidelines for citrus by comparing them to the Israeli orchard leaf mineral status using a 10‐year leaf‐mineral database (results of 20 244 leaf analyses from commercial orchards all over Israel). Then, we created an updated guideline using a second database (the Israeli National Wastewater Effluent Irrigation Surveys database; INWEIS). This database summarizes yield and leaf mineral concentrations of commercial orchards from all over Israel. The data were collected from 122 orchards: 39 orchards of "Oroblanco" Pomelit (Citrus grandis), 33 orchards of "Michal" mandarin (C. reticulata), 30 orchards of "Star Ruby" grapefruit (C. paradise), and 20 orchards of "Shamouti" oranges (C. sinensis) over a 7‐year period. Based on the first database, there was a disagreement between recommendations and the leaf nutrient status (e.g., the Israeli Ministry of Agriculture recommendations were higher than orchard median values), which indicated that the growers and/or the recommendations need to be corrected. Based on the INWEIS database, a new guideline was set. It was found that the optimal leaf nutrient concentrations for grapefruit trees are 1.7% to 2.1% dry weight (DW) for N, 0.08% to 0.010% DW for P, 0.37% to 0.48% DW for K, and 0.33% to 0.45% DW for Mg. For orange trees, the optimal leaf nutrient concentrations are 1.9% to 2.3% DW for N, 0.11% to 0.14% DW for P, 0.80% to 1.00% DW for K, and 0.19% to 0.26% DW for Mg. For mandarin trees, the optimal leaf nutrient concentrations are 2.0% to 2.4% DW for N, 0.09% to 0.12% DW for P, 0.55% to 0.69% DW for K, and 0.19% to 0.26% DW for Mg. Maintaining leaf nutrient concentrations within these ranges will support maximal yields of 110 to 120 t ha–1 for grapefruit, 65 to 70 t ha–1 for orange, and 60 to 70 t ha–1 for mandarin cultivars.